Target selection from airborne magnetic and radiometric data in Steinhausen area, Namibia - Naudé, Corus (Rhodes University, Faculty of Science, Department of Geology, 2013)
The eastern branch of the late Proterozoic Damara Orogenic Belt of central Namibia hosts various copper, gold, manganese and uranium deposits, but in the vicinity of Steinhausen, approximately 145 km northeast of Windhoek, the Damara Belt becomes increasingly covered by recent Kalahari cover sediments resulting in little known geology and subsequent lack of discovered economic mineral deposits. Airborne magnetic and radiometric data over the Steinhausen Study Area was enhanced through image processing and filtering to accentuate characteristics of subsurface geology that, by comparing these characteristics to known geology, aided in the interpretive mapping of lithology, structure and targets for follow-up exploration. As a result, some important observations regarding the regional lithology can be drawn. An arenaceous stratigraphic unit that includes a coarse grained, glassy quartzite below the Kuiseb Formation equates to either the eastern Damaran equivalent of the Nosib Group subjected to high grade metamorphism or, alternatively, the upper part of the pre-Damaran sequence, immediately underlying the Damara. The Kuiseb Formation within the study area is uncharacteristically varied as compared to the same formation further west along the Damaran Orogen and can be subdivided into 5 separate units based on geophysical signature. Structural features evident within the study area include the prominent Kudu and Okahandja Lineaments and straddle an area of inferred uplifted stratigraphy of possibly pre-Damara age. The Ekuja Dome (Kibaran age and host to the Omitiomire copper deposit) is also clearly discernible on the airborne magnetic data and is cross-cut by an east-northeast structural zone. Direct targets for follow-up exploration include the Rodenbeck intrusion, anomalous magnetic bodies and numerous radiometric anomalies present within the study area. Identified dome-like features are considered prospective for Omitiomire-style deposits and the Okatjuru Layered Complex is considered a possible source of copper, chromite, magnetite, ilmenite, nickel and the platinum group elements.
Keywords: Geomagnetism -- Maps -- Namibia; Geological surveys -- Namibia; Magnetometers; Aeromagnetic prospecting -- Namibia